Microsoft Office 2010 introductory - Shelly, Gary B. (Shelly Cashman series, 2011)
Features of this book include: A step-by-step, screen-by-screen approach allowing students to successfully learn and retain information to be used in their personal and professional lives; New opening chapter presents Office 2010 and Windows 7 skills preventing coverage of basic skills in the applications chapters and providing students with a strong base for further learning; Expanded coverage of PowerPoint and Outlook provides a thorough introduction to these applications and gives exposure to the numerous enhancements made to Office 2010; Chapter topic redistribution offers concise chapters that ensure complete skill coverage and lead to more manageable chapters; New pedagogical elements enrich material and create an accessible and user-friendly approach allowing easy navigation through the skills in each chapter.